Universal Priesthood of Christians and Ministry of the Church: Assessments marked out in the theology of Martin Luther - Fischer, Gerson Joni (Vox Scripturae - Revista Teológica Internacional, 2025)
We appreciate the understanding of the reformer Luther on the theme of the Universal Priesthood and Church Ministry. Do the services that the church ordain for its operation only arise from the priesthood common to those who believe? The hypothesis of this article is auscultated that it is not possible to find justification that establishes another foundation for the ecclesiastical ministry. The priesthood of Christians comes from the high priest Jesus. It is a gift, by God instituted for his praise; is participation in the ministry of reconciliation. To be a Christian corresponds to being born a priest by faith: a reality that begins in the presence of God, and then takes place among people. In Luther’s theology, the subject opens possibilities for reflection on the organization of church life and work. The ministry attributed to certain people does not communicate to them a higher power, since the service of mutual support for living the faith is not limited to them. The only boundary of the ministry is that which promotes community life. Priest in service is the Christian taught by God to live in freedom, integrated into an exhortative community circle. The purpose of the church, according to the New Testament, should always be to multiply the ministries. The Word that has been entrusted by God to all and by them is announced, but needs a specific ordination of people to promote it. How many are needed should be chosen to take on ministerial functions. This is a requirement of order. But after all, was the ministry of the Word entrusted to the whole church or only to some? It is maintained that there is no contradiction in Luther’s thought, since every kind of ministry emerges from the Universal Priesthood: the service of all demands that of some in the name of others. The obvious tension needs to be maintained and can be proactive, for the ministry of some is the same as that assigned by God to the whole church. Prayer and mutual exhortation present themselves as a way for the ministry not to be transformed into a field of conflict and desideratum, a manifestation of the nefarious desires that are hidden in human nature.